The Role of NGOs in International Relations and Public Diplomacy - N. V. Burlinova (Международная аналитика)
The paper examines Russia’s and the EU’s approaches to non-governmental organizations (NGOs) as instruments of public diplomacy (PD). As the EU and Russia increasingly instrumentalize NGOs in their foreign policy, which seems to erode trust in their already burdened relations, the topic presents an opportunity to compare the mechanisms of government–NGO interaction in Russia and EU. The specifi c forms, roots, and aims of this phenomenon have often been overlooked in academic research. To these ends, the author looks into diff erent views and practices of Brussels and Moscow in terms of supporting and fi nancing NGOs in the sphere of public diplomacy. The study demonstrates that the EU’s approach is characterized by signifi cant funding of NGOs abroad as part of governmental public diplomacy eff orts. On the other hand, the Russian approach is mostly characterized by funding of national NGOs, which then implement public diplomacy projects aligned with government policies abroad.